2020
DOI: 10.18502/ijph.v49i8.3866
|View full text |Cite
|
Sign up to set email alerts
|

Infertile Women’s Opinion Concerning Gestational Surrogacy: A Systematic Review and Meta-Analysis

Abstract: Background: This systematic review and meta-analysis of the observational studies aimed at evaluating the infertile women’s attitude toward gestational surrogacy. Methods: Published studies until Jan 2019 were searched using PubMed/MEDLINE, Scopus, EMBASE, Cochrane Library, ISI Web of Science, Proquest and Google scholar, MagIran, SID and IranMedex. Studies in English or Persian language surveyed attitudes toward surrogacy for infertile women published until Jan 2019. Animal studies and studies with poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is recognized that lack of transparency in the structure of joint processes between different sections of society and the health sector may be an obstacle to proper decision making [14]. Musavi et al in a study concluded that the lack of transparency in the structure of participatory activities is a major obstacle in setting operational goals [12]. The reason for emphasizing transparency in the structure is to facilitate the various stages of planning and policymaking, as well as the implementation of joint programs related to maternal health [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized that lack of transparency in the structure of joint processes between different sections of society and the health sector may be an obstacle to proper decision making [14]. Musavi et al in a study concluded that the lack of transparency in the structure of participatory activities is a major obstacle in setting operational goals [12]. The reason for emphasizing transparency in the structure is to facilitate the various stages of planning and policymaking, as well as the implementation of joint programs related to maternal health [15].…”
Section: Discussionmentioning
confidence: 99%
“…During the participatory process, when common goals are not properly defined or financial disputes arise, members may experience a variety of operational conflicts that require proper management to access the goals [12]. One of the participants said that: "Different goals, perspectives and interests may create different perceptions of the stakeholders and lead to conflict, in some cases;…”
Section: Intersectoral Conflict Managementmentioning
confidence: 99%
“… 63 195 196 Curiously, a recent meta-analysis showed that the majority of infertile women were not in favor of surrogacy. 197 198 A study in Romania revealed that women (general population) would rather adopt than resort to surrogacy. 199 On the other hand, studies with Iranian infertile couples reported that the majority has a positive view on surrogacy.…”
Section: Ethical Issuesmentioning
confidence: 99%